Upon a spring breeze - Irvin, Kelly (Irvin, Kelly. Every Amish season novel., 2017)
Bess Weaver, 20 and expecting her first child, is in the kitchen making stew for her beloved mann, Caleb, one minute, and the next, she's burying him after a tragic accident. Facing life as a young widow, Bess finds comfort only in tending the garden at an Englisch-owned bed and breakfast - even as she doubts that new growth could ever come after such a long winter. Aidan tries to repress his guilt over his best friend Caleb's death and his long-standing feelings for Bess by working harder than ever. But as he spends time with the young son his friend left behind, he seems to be growing closer to the boy's beautiful mother as well. When a close-knit group of widows in her Amish community step in to help Bess find her way back to hope, she begins to wonder if Gott has a future for her after all. Will she ever believe life can still hold joy and the possibility of love?